Early traffic sampling algorithm based on SSCBF - Ying HOU; Yun-fei GUO; Hai HUANG; Kai WANG (Tongxin xuebao)
An early traffic sampling algorithm was proposed based on same source and combination Bloom filter (SSCBF),a structure with two Bloom filters:flow-sampling vector and packet-count vector.The hash functions of the two vectors were same but the counters’ widths were different.This structure separated the sampling judgment and the packets counting.That could avoid the interference with packet count vector by the finished sampling flows.The false positive rate of the algorithm and an adjustable parameter α,ratio of the two vectors’ widths,were analyzed.The analysis and experiments demonstrate that with suitable α,the algorithm can achieve higher accuracy without increasing the space complexity.